Currículo e educação especial: as ações da escola a partir dos diálogos cotidianos - Vieira, Alexandro Braga (2012)
This study aimed at investigating the actions of a public elementary school in order to involve students with disabilities and pervasive developmental disorders in the school curriculum. It was based on the theoretical contributions by Boaventura de Sousa Santos, Michel de Certeau and Philippe Meirieu in order to have a sociological, philosophical and pedagogical discussion about the situations started by this investigation. In the curricular field, this study is founded on the theories by Silva, Moreira, Apple and Sacristán among other theoreticians who also analyze knowledge work in the school setting. In the Special Education field, it discusses productions by researchers who advocate the idea that the school inclusion process implies access to school, as well as permanence and the right to acquire knowledge that is socially produced. Collaborative critical action research was adopted as theoreticalmethodological framework, which maintains that, through scientific research, one can produce knowledge about social reality, promote changes in challenging situations, and involve study individuals into continuing education processes. The investigation was carried out in an elementary school of the Municipal Public School Network in Vila Velha, ES, Brazil, and it involved teachers, pedagogues, school principal, parents and guardians, and students enrolled in 1st to 6th grades. Data production process took place from July 2010 to July 2011. The researcher was in the school three times a week participating in classroom interventions, continuing education planning, and in informal occasions such as students’ arrival/leaving and playtime. Three correlated approaches were employed so as to carry out the study: participant observation and listening to discourses of students, teachers, technical-pedagogical team, and parents or guardians about the involvement of students recommended for Special Education in the school curriculum; monitoring spaces for continuing education and using the data produced in the first stage of the study as elements to support formative dynamics; supervising the school actions that aim at including educational needs of special education students in the school curriculum, which are based on reflections started in the spaces for continuing education. The results show the necessity of advocating a school curriculum that is more open to meet the learning needs of students with physical, psychic, intellectual or sensorial disabilities. This research is far from the line of reasoning that defends curricular flexibility such as emptying the curriculum in the name of students' conditions. We understand that between school curriculum and knowledge production by special education students there is a variety of situations that need to be analyzed by the school, such as texts produced about students’ learning; poor knowledge about human sexuality; challenges in the relationship between school and families; and the concept of normal/abnormal. These factors can be elements that hinder students’ success in their educational journey. However, they can also be used as questions to support continuing education. The study shows that through collaborative and critical action among school professionals it is possible to integrate actions that grant students with disabilities and pervasive developmental disorders the right to learn in a regular school.